The viscoelastic properties of cork - Mano, J F (Journal of materials science, 2002)
The viscoelastic properties of cork (from Quercus suber) have been investigated in the temperature range −40 to 120 ◦ C using the technique of Dynamic Mechanical Analysis (DMA). The results were compared with dielectric data previously reported. A relaxation was detected with a maximum in tan δ at ca 20 ◦ C (f = 1 Hz) and with a mean activation energy of 140 kJ ·mol−1 . A decrease in the intensity of the relaxation and an increase of the storage modulus is observed when cork is previously subjected to an annealing process above 60 ◦ C. This result is in agreement with previously reported dielectric data. Thermogravimetric experiments seem to conﬁrm that such effect could be caused by the desorption of water molecules. Specimens oriented along the prismatic direction presented higher storage modulus than the ones oriented along the transverse prismatic direction. The rheological properties of cork also showed a dependence upon the mechanical mode used during measurements: for example, the stiffness is the highest for the tensile mode and the lowest for the compression mode.
Keywords: Cork; Dynamic mechanical analysis (DMA); Relaxation; viscoelastic properties (voyant)

The viscoelastic properties of cork - Mano, J. F. (Journal of materials science, 2002)
The viscoelastic properties of cork (from Quercus suber) have been investigated in the temperature range −40 to 120 ◦ C using the technique of Dynamic Mechanical Analysis (DMA). The results were compared with dielectric data previously reported. A relaxation was detected with a maximum in tan δ at ca 20 ◦ C (f = 1 Hz) and with a mean activation energy of 140 kJ ·mol−1 . A decrease in the intensity of the relaxation and an increase of the storage modulus is observed when cork is previously subjected to an annealing process above 60 ◦ C. This result is in agreement with previously reported dielectric data. Thermogravimetric experiments seem to conﬁrm that such effect could be caused by the desorption of water molecules. Specimens oriented along the prismatic direction presented higher storage modulus than the ones oriented along the transverse prismatic direction. The rheological properties of cork also showed a dependence upon the mechanical mode used during measurements: for example, the stiffness is the highest for the tensile mode and the lowest for the compression mode.
Keywords: Cork; Dynamic mechanical analysis (DMA); Relaxation; viscoelastic properties (voyant)

Spectral editing of 13C cp/MAS NMR spectra of complex systems: application to the structural characterisation of cork cell walls. - Lopes, M H; Sarychev, A; Neto, C P; Gil, A M (Solid state nuclear magnetic resonance, 2000)
A mathematical method of obtaining 13C CP/MAS subspectra of single components of a complex system is presented and applied to three- and four-component systems. The method is based on previously reported work that exploits different proton relaxation properties for different domains of an heterogeneous system. However, unlike the original method that obtained subspectra through a trial-and-error approach, the method here presented solves the problem mathematically, thus avoiding the time-consuming and non-rigorous trial-and-error step. The method is applied to mixtures of three and four polymers and to a more complex system: cork cell walls. As expected, as the number of components increases, the sharing of relaxation properties between different components is increasingly probable, either due to incidental coincidence of relaxation times or to specific interactions and intimate mixing of compounds. While this hinders the calculation of the subspectra of single chemical components, it may provide useful information about inter-component interactions. This possibility was demonstrated by the application of this method to cork cell walls. Both three-component and four-component approaches showed that three domains exist in cork cell walls: carbohydrate/lignin matrix, mobile suberin close to (probably bonded to) lignin groups (about 42% w/w) and hindered suberin close to (probably bonded to) carbohydrate-OCH2O groups (about 4% w/w).
Keywords: 13CCPrMAS NMR; Cork; Polymer; Quercus suber L.; Relaxation; Spectral editing

Spectral editing of 13C cp/MAS NMR spectra of complex systems: application to the structural characterisation of cork cell walls. - Lopes, M. H.; Sarychev, A.; Neto, C. P.; Gil, a M. (Solid state nuclear magnetic resonance, 2000)
A mathematical method of obtaining 13C CP/MAS subspectra of single components of a complex system is presented and applied to three- and four-component systems. The method is based on previously reported work that exploits different proton relaxation properties for different domains of an heterogeneous system. However, unlike the original method that obtained subspectra through a trial-and-error approach, the method here presented solves the problem mathematically, thus avoiding the time-consuming and non-rigorous trial-and-error step. The method is applied to mixtures of three and four polymers and to a more complex system: cork cell walls. As expected, as the number of components increases, the sharing of relaxation properties between different components is increasingly probable, either due to incidental coincidence of relaxation times or to specific interactions and intimate mixing of compounds. While this hinders the calculation of the subspectra of single chemical components, it may provide useful information about inter-component interactions. This possibility was demonstrated by the application of this method to cork cell walls. Both three-component and four-component approaches showed that three domains exist in cork cell walls: carbohydrate/lignin matrix, mobile suberin close to (probably bonded to) lignin groups (about 42% w/w) and hindered suberin close to (probably bonded to) carbohydrate-OCH2O groups (about 4% w/w).
The following values have no corresponding Zotero field: accession-num: 10868562
Keywords: 13CCPrMAS NMR; Cork; Polymer; Quercus suber L.; Relaxation; Spectral editing

Very high-resolution 1H MAS NMR of a natural polymeric material - Gil, A M; Lopes, M H; Pascoal Neto, C; Rocha, J (Solid State Nuclear Magnetic Resonance, 1999)
The use of ultrafast magic angle spinning (>30 kHz) in tandem with delayed echo acquisition is shown to yield very high-resolution 1H MAS NMR spectra of complex natural organic materials. For the first time, very high-resolution 1H MAS NMR spectra are reported for cork and wood components, two natural materials with great economic importance. The effect of the spinning rate on the 1H NMR spectra was evaluated with single-pulse acquisition and delayed-echo acquisition. The delayed-echo acquisition spectra presented linewidths as sharp as 67 and 25 Hz. The narrow peaks, characterised by proton spin–spin and spin–lattice relaxation, were assigned to the isotropic chemical shifts and the general spectral features were shown to correlate with the sample chemical structure. The tentative assignments of cork 1H MAS NMR signals were presented.
Keywords: 1H MAS NMR; Cellulose; Cork; Lignin; Relaxation; suberin